Gambaran Persepsi Ibu Terhadap Kunjungan Imunisasi Dasar pada Masa Pandemi Covid-19 di Wilayah Kerja Puskesmas Naioni - Nurti Nabunome; Honey I. Ndoen; Amelya B. Sir (Yayasan Literasi Sains Indonesia, 2023)
During the COVID-19 pandemic, there was a decrease in basic immunization visits during the pre-pandemic and post-pandemic periods. IDL coverage decreased from 68,9% in 2019 to 60,8% in 2021, while HB-0 basic immunization visits decreased from 39,7% to 10,4%.Immunizations must still be carried out even during the COVID-19 pandemic. The purpose of the research is to describe mother's perception of basic immunization visits during the COVID-19 pandemic in the working area of Naioni Health Center, Kupang City. Type of this research is descriptive quantitative with a Cross Sectional research design. The population of this research are the mothers who had babies aged 0-11 months and live in the working area of the Naioni Health Center in December 2021 with totals 267 people. The sampling technique used is simple random sampling with a sample size of 73 people. Data analysis used univariate analysis. The results showed that mothers with a high perceived suspectibility is more visit (87,0%), mothers with a high perceived severity is more visit (65,2%), mothers with a high perceived benefits is more visit (78,3%), mothers with a high perceived barriers is more visit (87,0%), mothers with a high self-efficacy is more visit (95,7%) and mothers with a high cues to action is more visit (52,2%) during the COVID-19 pandemic. Therefore, Health Center plays a role to increase mothers perception and basic immunization visits according to the type and time of administration.